2015
DOI: 10.1007/s11605-015-2832-1
|View full text |Cite
|
Sign up to set email alerts
|

Donor Hepatic Steatosis and Outcome After Liver Transplantation: a Systematic Review

Abstract: Available evidence showed increased risk of poor graft outcome in moderate-severe steatotic livers. A large prospective multi-centred trial will be required to identify the true risks of steatotic livers. Consistent definition of primary non-function/impaired primary function and description of type of steatosis is also required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(151 citation statements)
references
References 56 publications
2
137
1
4
Order By: Relevance
“…In liver transplantation, the presence of macro scopic hepatic steatosis can have serious consequences and increase the risk of primary graft nonfunction 8 , the more severe the steatosis then the greater the risk of hepatic dysfunction. A proportion of potential liver donor grafts have to be discarded if they are too fatty, as above a threshold of steatosis there is an increased risk of graft failure upon transplantation 79,80 . The assess ment of steatosis can be made by the surgeon at the time of organ procurement, but has an inbuilt subjective element.…”
Section: Fatty Livermentioning
confidence: 99%
“…In liver transplantation, the presence of macro scopic hepatic steatosis can have serious consequences and increase the risk of primary graft nonfunction 8 , the more severe the steatosis then the greater the risk of hepatic dysfunction. A proportion of potential liver donor grafts have to be discarded if they are too fatty, as above a threshold of steatosis there is an increased risk of graft failure upon transplantation 79,80 . The assess ment of steatosis can be made by the surgeon at the time of organ procurement, but has an inbuilt subjective element.…”
Section: Fatty Livermentioning
confidence: 99%
“…Another possible use is in the setting of orthotopic liver transplantation for assessment of fatty liver grafts [10]. It has been shown that >30% hepatic steatosis is associated with decreased graft survival [41]. Hence, a reliable tool for intraoperative evaluation of liver steatosis is required.…”
Section: Discussionmentioning
confidence: 99%
“…Para utilizar un órgano con tranquilidad con un mínimo impacto en el resultado postrasplante, la mayoría de los grupos acepta en un donante la presencia de esteatosis macrovacuolar leve o menor del 30% (16). Mientras que con esteatosis moderada (mayor del 30% pero menor del 60%), su uso es muy discutido, la incidencia de disfunción primaria puede llegar al 15% y la tasa de la función retardada del injerto se aproxima al 35%.…”
Section: Aspectos Histopatológicos Más Frecuentes Que Pueden Observarunclassified